Dating in the Craven Dales. (24th January 2013) - Wilson, Peter; Lord, Tom C.; Telfer, Matt W.; Barrows, Timothy T.; Vincent, Peter J.
<x xml:space="preserve">Abstract</x> The Craven Dales of North Yorkshire contain some of the finest examples of limestone geology and landscape in the UK. The extensive limestone pavements with their clints, grikes and other water‐worn features, are a key attraction for both scientists and recreational visitors. Likewise the cave systems attract attention with their remarkable sediment accumulations, some of which are in excess of 500 000 years old and others contain the bones of mammals that are either extinct or no longer present in the British Isles. The glacial erratic boulders at Norber and the loessic sediments that, in places, mask the limestone have also provided stimulus for investigation. Summarized below are the findings of several recent studies that focussed on establishing the age of various features. Whilst the reports answer some long‐standing questions, they also demonstrate that there is still much that can be learned about this seemingly familiar territory.